Impact of educational intervention in reducing the weight of school bags in selected school children - Meenakshi; Sushma K Saini; Bhavneet Bharti; Nirmal R Gopinathan; Kavita (Wolters Kluwer Medknow Publications, 2023)
Background: To assess the effectiveness of educational intervention to reduce the weight of school bags. Material and Methods: The study design was one group pre- and posttest experimental Research design. Place and Duration of Study: Government Senior Secondary School Dhanas, Chandigarh, and Shri Guru Harkrishan Model Senior Secondary School Sector-38D, Chandigarh (A private school) between July and November 2018. Names of the schools can be avoided. Total 760 students from selected sections nursery to 10th class of school were enrolled in the study. At baseline and end line weight of children, school bags and its content were weighed using weighing scale. Length of bag strap, breath of bag, torso of children, and their shoulders size were measured by measuring tape. Bag carrying style, posture, etc., were observed by observation checklist. Interviewed children (5th to 10th class) were using Nordic musculoskeletal questionnaire for musculoskeletal system assessment. Educational intervention was provided to the children for one month to reduce weight of school bag by teaching in assembly and displaying the charts in school. (Use of softbound thin textbooks, breaking thin books in 2-3 thin softbound books, use lightweight bag, pencil box, lunch box, and water bottles. Pack bag as per timetable.) Result: The result revealed that heavy school bags were carrying 69.7% children from government school and 80.2% from private school. Children carrying heavy bags reported musculoskeletal problems 5 times higher than their counterparts. After intervention, there was significant reduction in the weight of school bags (P < 0.001 as per paired t-test). Provide the weight of the bags before and after intervention in addition to the P value. Conclusion: Children carrying heavy bags were suffering from musculoskeletal problems. Intervention helped in reducing the weight of school bag.